Construction of Mn0.5Zn0.5Fe2O4 modified TiO2 nanotube array nanocomposite electrodes and their photoelectrocatalytic performance in the degradation of 2, 4-DCP1. Issue 23 (21st June 2015) - Pan, Jingqiang; Li, Xinyong; Zhao, Qidong; Li, Tingting; Tade, Moses; Liu, Shaomin
<x xml:space="preserve">Abstract</x> Mn0.5Zn0.5Fe2O4 contributes to the enhanced photoelectrochemical properties and photoelectrocatalytic activity of TiO2 nanotube arrays.